Influence of nanofluid properties on turbulent forced convection heat transfer in different base liquids - Sharma, K.V. (John Wiley and Sons Ltd, 2020)
This paper analyses the influence of nanofluid properties on turbulent convective heat transfer characteristics for various base fluids. The turbulent characteristics of heat transfer and flow have been determined by applying the Van Driest model of the eddy diffusivity for water and ethylene glycol-based nanofluids. The properties of CuO, Al2O3 and SiO2 nanofluids in two base liquids (water and EG-water mixture with the ratio of 60:40) have been considered for various concentrations, as well as large temperature ranges. Based on the observations, it is concluded that numerical outcomes are validated with experimental measurements for heat transfer properties. It is also established that SiO2 reaches a higher temperature gradient in comparison with CuO at a similar temperature and concentration in EG-water, with the mixture of 60:40. The gradients are greater for the EGW mixture compared to water-based nanofluids. However, the water-based nanofluids have higher heat transfer coefficients compared to EG-water nanofluid at identical flow velocities. It is also notable that the key findings demonstrate that for the heat transfer coefficient, especially in practical situations, the use of nanoparticles and the base fluids tends to enhance the parameter of the coefficient of heat transfer. Also, this study is deemed contributory to the literature and extends the works of some of the previous scholarly contributors by affirming that the factor or parameter concerning the coefficient of heat transfer has its values or behavior dependent on the ratio between the water base liquid and the EG. Overall, it is shown that for higher values of the coefficient of heat transfer to be obtained, there is a need for the introduction of base liquids and nanoparticles, especially because these materials come with or exhibit superior thermal conductivity. Â© 2020 John Wiley & Sons, Ltd.